Marriage Discourses : Historical and Literary Perspectives on Gender Inequality and Patriarchic Exploitation - Jacob, Frank; Mohammed, Jowan A.; Jacob, Frank; Mohammed, Jowan A. (Berlin/Boston De Gruyter, 2021)
Marriage was historically not only a romantic ideal, but a tool of exploitation of women in many regards. Discourses about marriage in history and literature naturally became more and more heated, especially during the (3z(Blong(3y (B19th century. The present volume provides a discussion of the marriage discourses in different chronological and geographical contexts and shows which arguments played an important role in the demand for more equality.s
English
Keywords: Literature & literary studies; History; General & world history; Modern history to 20th century: c 1700 to c 1900; Social & cultural history; Gender studies, gender groups; Marriage discourses; marriage; marital relations; gender roles